Inflammation and Oxidative Stress in Cardiac Surgery Patients Treated to Intensive Versus Conservative Glucose Targets - Reyes-Umpierrez, David (J Clin Endocrinol Metab, 2016)
OBJECTIVE: We aimed to determine (a) longitudinal changes of inflammatory and oxidative stress markers and (b) the association between markers of inflammation and perioperative complications in coronary artery bypass surgery (CABG) patients treated with intensive vs conservative blood glucose (BG) control. METHODS: Patients with diabetes (n = 152) and without diabetes with hyperglycemia (n = 150) were randomized to intensive (n = 151; BG: 100–140 mg/dL) or to conservative (n = 151; BG: 141–180 mg/dL) glycemic targets. Plasma cortisol, high-sensitivity C-reactive protein (hsCRP), tumor necrosis factor-α, interleukin-6 (IL-6), thiobarbituric acid-reactive substances, and 2′-7′-dichlorofluorescein were measured prior to and at days 3, 5, and 30 after surgery. RESULTS: Intensive glycemic control resulted in lower mean BG (132 ± 14 mg/dL vs 154 ± 17 mg/dL, P < 0.001) in the intensive care unit. Plasma cortisol and inflammatory markers increased significantly from baseline after the third and fifth day of surgery (P < 0.001), and returned to baseline levels at 1 month of follow-up. Patients with perioperative complications had higher levels of cortisol, hsCRP, IL-6, and oxidative stress markers compared with those without complications. There were no significant differences in inflammatory and oxidative stress markers between patients, with or without diabetes or complications, treated with intensive or conventional glucose targets. CONCLUSION: We report no significant differences in circulating markers of acute inflammatory and oxidative stress response in cardiac surgery patients, with or without diabetes, treated with intensive (100–140 mg/dL) or conservative (141–180 mg/dL) insulin regimens.